(untitled) (Tạp chí Y học Cộng đồng, 2024)
Objectives: to determine the prevalence of cervical cancer screening in low and middle-income countries. Method: This literature review was conducted in accordance with the Cochrane Collaboration guidance for literature reviews and reported following the PRISMA statement. We conducted searches of electronic bibliographic databases including Pubmed, Embase, MEDLINE, Cochrane Systematic Reviews and Cochrane CENTRAL. Results: Our searches of the listed electronic databases generated 7,845 records. 23 studies met the inclusion criteria. The total sample size of female participants was 213,199. The definition of screening definitions were relatively similar among studies. Screening rates varied between studies (from 4% to 43%). The Pap smear test was the most common screening modality, next was Visual Inspection Acetic Acid (VIA). The overall prevalence of cervical cancer screening was still remarkably low 21.85% (95%CI: 20.56 - 22.32, I2 = 40%, p <0.001). Conclusions: Despite global efforts to make screening approaches affordable and accessible, most women in low- and middle-income countries are not screened for cervical cancer.